(untitled) (Communications in Computational Physics, 2020)
Stent placement is considered as a promising and minimally invasive technique to prevent rupture of aneurysm and favor coagulation mechanism inside the aneurysm. Many scholars study the effect of the stent on blood flow in cerebral aneurysm by numerical simulations, and usually regard blood as the Newtonian fluid, blood, however, is a kind of non-Newtonian fluid in practice. The main purpose of the present paper is to investigate the effect of non-Newtonian behavior on the hemodynamic characteristics of blood flow in stented cerebral aneurysm with lattice Boltzmann method. The Casson model is used to describe the blood non-Newtonian character, which is one of the most popular models in depicting blood fluid. In particular, hemodynamic characteristics derived with Newtonian and non-Newtonian models are studied, and compared in detail. The results show that the non-Newtonian effect gives a great influence on hemodynamic characteristics of blood flow in stented cerebral aneurysm, especially in small necked ones.